TRM versus FRP in flexural strengthening of RC beams: behaviour at high temperatures - Raoof, Saad M.; Bournas, Dionysios A. (Elsevier, 2017)
The flexural behaviour of RC beams strengthened with TRM and FRP composites was experimentally investigated and compared both at ambient and high temperatures. The investigated parameters were: (a) the strengthening material, namely TRM versus FRP, (b) the number of strengthening layers, (c) the textile surface condition (dry and coated), (d) the textile material (carbon, basalt or glass fibres) and (e) the end-anchorage of the flexural reinforcement. A total of 23 half-scale beams were constructed, strengthened in flexure and tested to assess these parameters and the effectiveness of the TRM versus FRP at high temperatures. TRM exhibited excellent performance as strengthening material in increasing the flexural capacity at high temperature; in fact, TRM maintained an average effectiveness of 55%, compared to its effectiveness at ambient temperature, contrary to FRP which totally lost its effectiveness when subjected to high temperature. In specific, from the high temperature test it was found that by increasing the number of layers, the TRM effectiveness was considerably enhanced and the failure mode was altered; coating enhanced the TRM effectiveness; and the end-anchorage at high temperature improved significantly the FRP and marginally the TRM effectiveness. Finally, the formula proposed by the Fib Model Code 2010 was used to predict the mean debonding stress in the TRM reinforcement, and using the experimental results obtained in this study, a reduction factor to account for the effect of high temperature on the flexural strengthening with TRM was proposed.